Optimization of the building ventilation of a bath treatment plant of an aluminium smelter using CFD modelling - E. Dernedde (Canadian Institute of Mining, Metallurgy and Petroleum, 2005)
Industrial plants located in the province of Quebec, Canada, are subjected to large variations of the ambient air temperature, Building ventilation systems of these plants must have some flexibility in order to meet industrial hygiene standards (TLV for chemical substances, heat stress and cold stress) at any time of the year, The building ventilation of a bath treatment plant of an aluminium smelter in Quebec was examined under summer and winter conditions, Part of the plant has periodic emissions of hydrogen fluoride gas and heat from hot anode butts, CFD modeling was used to optimise the building ventilation of the bath treatment plant, The present study proposes a modified building ventilation system, which improves the internal environment, complies with industrial hygiene standards and also reduces heating costs by 20 % during winter.